Development of Web-Based Advertisement Media on Sahrul Home Car Care - Bakhtiar, Yohan; Izzah, Abidatul; Cinderatama, Toga Aldila; Nugroho, Benni Agung; Susanto, Riswan Eko Wahyu (Journal of Applied Business and Technology, 2023)
Amidst the ongoing Covid-19 pandemic, non-essential activities have shifted mainly to the safety of people's homes. This includes remote work (Work From Home) and shopping for basic needs online. However, service workers, particularly those in the service sector like Muhammad Sahrul, have faced significant challenges navigating the pandemic's impact. Sahrul, who owns an all-brand car repair shop, experienced a decline in customers visiting his workshop due to the outbreak. Recognizing the need for a fresh approach, Sahrul created "Sahrul Home Car Care," offering car repair services at customers' residences. To support this initiative, a team of researchers proposed technology-based solutions to improve his advertising strategy. The researchers developed a user-friendly digital portal, www.sahrulhomecarcare.com, showcasing Sahrul's services and implementing an appointment booking system. Additionally, they guided leveraging digital marketing channels to expand his outreach. Thanks to these digital innovations, Sahrul's business gained traction, attracting more customers and positive feedback. Embracing technology proved instrumental in overcoming the pandemic's challenges and ensuring the continued success of "Sahrul Home Car Care" in this ever-evolving digital era.